2003
DOI: 10.1177/014107680309600908
|View full text |Cite
|
Sign up to set email alerts
|

Troubles with the Foreskin: One Hundred Consecutive Referrals to Paediatric Surgeons

Abstract: To assess the reasons for and outcomes of referrals concerning the foreskin, 100 consecutive patients seen in paediatric clinics were followed to discharge. 18 referrals were for circumcision on religious grounds. Of the other 82, the main reason for referral was non-retractability or phimosis. At clinic, 24 (29%) of these were deemed normal for age, 31 (38%) were treated with topical steroid (successfully in 25), 9 (11%) were listed for preputioplasty, 7 (9%) were listed for adhesiolysis, 7 (9%) were listed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Specifically, in our series, the prevalence of BXO was more than double that in previous, comparable series (12.1% versus 5-6%) whilst circumcising a greater proportion of boys (35.1% versus 9-25%). 2,12 Other published series from British centres have reported circumcising boys presenting with preputial problems in similar proportions to our series (28-34%) series but these give no figures for the prevalence of BXO. 14,15 The number of young children circumcised was, however, higher than in other series, 11% of those presenting under 2 years and 20% of those between 2-4 years.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Specifically, in our series, the prevalence of BXO was more than double that in previous, comparable series (12.1% versus 5-6%) whilst circumcising a greater proportion of boys (35.1% versus 9-25%). 2,12 Other published series from British centres have reported circumcising boys presenting with preputial problems in similar proportions to our series (28-34%) series but these give no figures for the prevalence of BXO. 14,15 The number of young children circumcised was, however, higher than in other series, 11% of those presenting under 2 years and 20% of those between 2-4 years.…”
Section: Discussionsupporting
confidence: 72%
“…Published series of boys under 18 and 15 years, respectively, presenting for circumcision have found BXO in 5-6%. 2,12 We examined a consecutive series of boys presenting for consideration for circumcision to determine the nature of the work-load created and the management decisions made. We also reviewed the histological findings in the foreskins of those boys who were circumcised.…”
mentioning
confidence: 99%
“…Again, they have alluded to the inability of primary care physicians to adequately differentiate between true pathological phimosis and a physiological non-retractile prepuce. 7 Although not employed in the present study, the antiinflammatory and immunosuppressive effects of topical steroid application has generated considerable interest in the treatment of childhood phimosis. Various preparations of betamethasone, clobetasol, mometasone furoate and triamcinolone acetonide have been used; betamethasone being the most widely studied and associated with the best results.…”
Section: Discussionmentioning
confidence: 96%
“…[82] In contrast to a reported rate of 1%,[83] two UK studies found LS prevalence of 5% and 6% in uncircumcised boys under 18 and 15 years of age, respectively. [8485] Histological examination of foreskins removed for various reasons revealed LS in 3.6%–19%. [868788899091] A study in Plymouth, UK, of 422 boys aged 3 months to 16 years (mean 6 years) referred to a pediatric general surgical outpatient department with foreskin problems found 55.9% were normal, with the remainder (44.1%) undergoing surgery: 35% circumcision, 8% preputial adhesiolysis, and 0.1% frenuloplasty.…”
Section: Resultsmentioning
confidence: 99%